Development and validation of a parent-proxy health-related quality of life survey for Australian First Nations children - Anne B Chang; Lee Jones; Maree Toombs; Kerry-Ann F O'Grady; Peter A Newcombe; Jeanie K Sheffield; Kaley Butten; Newell W Johnson; Anna Maria Bell; Greggory Ross (BMJ Open, 2021)
Objective Within Australia, Aboriginal and Torres Strait Islander (First Nations) populations perceive health and well-being differently to non-Indigenous Australians. Existing health-related quality of life (HR-QoL) measurement tools do not account for these differences. The objective of this study was to develop and validate a culturally specific parent-proxy HR-QoL measurement tool for First Nations children.Design Scale development was informed by parents/carers of children with a chronic illness and an expert panel. The preliminary 39-item survey was reviewed (n=12) and tested (n=163) with parents/carers of First Nations children aged 0–12 years at baseline with comparative scales: the Kessler Psychological Distress Scale, generic HR-QoL (Paediatric QoL Inventory 4.0, PedsQL4.0) and Spence Children’s Anxiety Scale, and repeated (n=46) 4 weeks later. Exploratory Factor Analysis was used for scale reduction. Reliability and validity were assessed by internal consistency, test–retest, and correlations with comparison scales.Results Items within our First Nations-Child Quality of Life (FirstNations-CQoL) were internally consistent with Cronbach’s alpha coefficients of ≥0.7 (quality of life, 0.808; patient experience, 0.880; patient support, 0.768) and overall test–retest reliability was good (r=0.75; 95% CI 0.593 to 0.856). Convergent validity was observed with the PedsQL4.0 with Pearson’s coefficients of r=0.681 (ages 2–4 years); r=0.651 (ages 5–12 years) and with the Kessler Psychological Distress scale (r=−0.513). Divergent validity against the Spence Anxiety Scale was not demonstrated.Conclusions The FirstNations-CQoL scale was accepted by the participants, reliable and demonstrated convergent validity with comparison measures. This tool requires further evaluation to determine responsiveness, its minimal important difference and clinical utility.